Synergies of carbon neutrality, air pollution control, and health improvement — a case study of China energy interconnection scenario - Jianxiang Shen; Wenjia Cai; Xiaotong Chen; Xing Chen; Zijian Zhao; Zhiyuan Ma; Fang Yang; Shaohui Zhang (Global Energy Interconnection, 2022)
Climate change and air pollution are primarily caused by the combustion and utilization of fossil fuels. Both climate change and air pollution cause health problems. Based on the development of China, it is extremely important to explore the synergies of the energy transition, CO2 reduction, air pollution control, and health improvement under the target of carbon peaking before 2030 and carbon neutrality before 2060. This study introduces the policy evolution and research progress related to energy, climate change, and the environment in China and proposes a complete energy-climate-air- health mechanism framework. Based on the MESSAGE-GLOBIOM integrated assessment model, emission inventory and chemical transport model, and exposure-response function, a comprehensive assessment method of energy-climate-air- health synergies was established and applied to quantify the impacts of Chinese Energy Interconnection Carbon Neutrality (CEICN) scenario. The results demonstrate that, by 2060, the SO2, NOx and PM2.5 emissions are estimated to be reduced by 91 %, 85 %, and 90 % respectively compared to the business-as-usual (BAU) scenario. The direct health impacts brought by achieving the goal of carbon neutrality will drive the proactive implementation of more emission reduction measures and bring greater benefits to human health.